2018
DOI: 10.1016/j.chom.2017.11.006
|View full text |Cite|
|
Sign up to set email alerts
|

Dysbiosis-Associated Change in Host Metabolism Generates Lactate to Support Salmonella Growth

Abstract: During Salmonella-induced gastroenteritis, mucosal inflammation creates a niche that favors the expansion of the pathogen population over the microbiota. Here, we show that Salmonella Typhimurium infection was accompanied by dysbiosis, decreased butyrate levels, and substantially elevated lactate levels in the gut lumen. Administration of a lactate dehydrogenase inhibitor blunted lactate production in germ-free mice, suggesting that lactate was predominantly of host origin. Depletion of butyrate-producing Clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
180
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(210 citation statements)
references
References 62 publications
5
180
0
8
Order By: Relevance
“…This causes a reduction in butyrate which alters metabolic activity of enterocytes which usually rely on butyrate, as discussed above, and thus leads to increased oxygen availability, further supporting Salmonella growth [7]. Changes in enterocyte metabolism were found to generate lactate which, along with the increase in oxygen, Salmonella could use as an energy source with oxygen as the final electron acceptor [70]. Furthermore, it was recently reported that Salmonella can utilize microbiota-derived succinate and host-derived electron acceptors to enable a complete oxidative tricarboxylic acid (TCA) cycle [116].…”
Section: Metabolic Interplay Between Host Microbiota and Pathogensmentioning
confidence: 92%
See 1 more Smart Citation
“…This causes a reduction in butyrate which alters metabolic activity of enterocytes which usually rely on butyrate, as discussed above, and thus leads to increased oxygen availability, further supporting Salmonella growth [7]. Changes in enterocyte metabolism were found to generate lactate which, along with the increase in oxygen, Salmonella could use as an energy source with oxygen as the final electron acceptor [70]. Furthermore, it was recently reported that Salmonella can utilize microbiota-derived succinate and host-derived electron acceptors to enable a complete oxidative tricarboxylic acid (TCA) cycle [116].…”
Section: Metabolic Interplay Between Host Microbiota and Pathogensmentioning
confidence: 92%
“…Antibiotic treatment-induced dysbiosis can have widereaching effects, for example on inflammation, infection and responses to vaccination [70][71][72]. Antibiotics have been shown to affect SCFA-producing bacteria causing a decrease in SCFA abundance [73,74].…”
Section: Effect Of Commensal Metabolites On Host Immune Functionmentioning
confidence: 99%
“…The presence of redundant Llactate dehydrogenases in P. aeruginosa may represent an adaptation to the host environment, given the fact that host organisms such as humans and plants (18,29,30) primarily produce the L-enantiomer. Several studies have implicated L-lactate metabolism in bacterial virulence 275 during infections including Salmonella-induced gastroenteritis (13) and gonococcal infection of the genital tract (12). Our results suggest that both LldD and LldA utilize L-lactate in SCFM to promote PA14 growth (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The D-and L-enantiomers of lactate are generally associated with bacterial and metazoan metabolism, respectively, with L-lactate being the primary form produced in sites of microbial colonization such as the mammalian gut (13) and the airway of patients with the inherited 180 disease cystic fibrosis (25). We were therefore interested in the relevance of lactate dehydrogenase activity to the growth and morphogenesis of biofilms, which represent a major lifestyle assumed by commensal and pathogenic bacteria.…”
Section: Both Lldd and Llda Contribute To L-lactate Utilization Durinmentioning
confidence: 99%
“…Beneficial microbes prime ontogenesis of immunity (Iatsenko et al 2014;Sudo et al 1997), regulate the host inflammatory response (Olszak et al 2012), and aid in various digestive and metabolic processes (Hooper et al 2001;Russell & Rychlik 2001). Pathogenic microbes release toxins (Simon et al 2014), disrupt microbial community structure (Gillis et al 2018), and may contribute to human diseases such as diabetes, obesity, and inflammatory bowel disease (IBD), for example (Wu et al 2015). The complexity of host-microbe interactions, and significant consequences for host wellness when the relationships are perturbed, argue that many host-microbe relationships are, at least in part, a result of co-evolution.…”
Section: Introductionmentioning
confidence: 99%